The Dawn of New Age Tourism: An Analysis of Aotearoa - Pernecky, Tomas (Auckland University of Technology, 2004)
This thesis studies New Age tourism and New Age tourists in New Zealand. In order to better understand this phenomenon, the research reviews literature pertaining to spirituality, religious tourism, pilgrimage and sacred sites. Using the theory of strategic groups, the study also shows that New Age tourism is distinct from other forms of travelling. The thesis argues that as a New Age destination, New Zealand’s rich natural and cultural resources present immense potential for development. Key New Age attractions in the country are identified and future development prospects discussed. Although a relatively new phenomenon, the research contends that the New Age market is not homogenous and visitors exhibit differences in 'interest', 'experience' and 'profile characteristics’. Nevertheless, a dominant theme in all New Age travel appears to be the pursuit of unique and transcendental life knowledge. To analyze the New Age tourists in detail, the study employs two research methodologies. Quantitatively, the profile characteristics of tourists are scrutinized and a specialization index is adopted to delineate differences between market segments. It will be shown that New Age tourists comprise three distinct groups: the low, medium and highly specialized individuals. Qualitatively, the New Age visitors are analyzed by means of a phenomenological method. Through in-depth understanding of their motivations, needs and opinions, the New Age traveller is seen to be constantly in search of extraordinary and life-changing experiences. Overall, the thesis demonstrates that a corroborative methodology combining quantitative and qualitative techniques provides not only a holistic view of New Age tourism, but also invaluable empirical insights into this burgeoning field of contemporary travel.
Keywords: New Age consumers; New Age movement; Tourism New Zealand (Organization)